2016
DOI: 10.1111/gtc.12338
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone complex BAG2–HSC70 regulates localization of Caenorhabditis elegans leucine‐rich repeat kinase LRK‐1 to the Golgi

Abstract: Mutations in LRRK2 are linked to autosomal dominant forms of Parkinson's disease. We identified two human proteins that bind to LRRK2: BAG2 and HSC70, which are known to form a chaperone complex. We characterized the role of their Caenorhabditis elegans homologues, UNC-23 and HSP-1, in the regulation of LRK-1, the sole homologue of human LRRK2. In C. elegans, LRK-1 determines the polarized sorting of synaptic vesicle (SV) proteins to the axons by excluding SV proteins from the dendrite-specific transport machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In the latter case, we have found that Rab7L1/Rab29 is important for recruiting LRRK2 to the TGN, along with the clathrin-uncoating protein cyclin-G associated kinase (GAK) and the co-chaperone BAG5. This protein complex may be conserved as similar proteins are important for the recruitment of Lrk-1 to the golgi apparatus in C elegans [74], Importantly, Rab7L1 and GAK are nominated to be risk factors for sporadic PD [14]. Clearance of Golgi-derived vesicles by the LRRK2 complex including Rab7L1 is enhanced by mutations across all enzymatic domains of LRRK2 whereas hypothesis testing LRRK2 mutations, including those that are kinase dead or cannot bind GDP/GTP, were ineffective in TGN vesicle clearance [73].…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…In the latter case, we have found that Rab7L1/Rab29 is important for recruiting LRRK2 to the TGN, along with the clathrin-uncoating protein cyclin-G associated kinase (GAK) and the co-chaperone BAG5. This protein complex may be conserved as similar proteins are important for the recruitment of Lrk-1 to the golgi apparatus in C elegans [74], Importantly, Rab7L1 and GAK are nominated to be risk factors for sporadic PD [14]. Clearance of Golgi-derived vesicles by the LRRK2 complex including Rab7L1 is enhanced by mutations across all enzymatic domains of LRRK2 whereas hypothesis testing LRRK2 mutations, including those that are kinase dead or cannot bind GDP/GTP, were ineffective in TGN vesicle clearance [73].…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…Hsc70, a non-heat-inducible form of Hsp70 may also be necessary for neurite differentiation. Mutations in the BAG2-Hsc70 chaperone complex was found to cause synaptic vesicles, normally located in the axon, to appear in the spines and processes of dendrites (Fukuzono et al, 2016). Chaperones contribute a great deal to cytoskeletal stability, which is especially important for neurons to sustain their complex processes ( Table 2; Bakthisaran et al, 2015;Nefedova et al, 2015;Nefedova et al, 2017;Kelliher et al, 2019;Muranova et al, 2019;Vallin and Grantham, 2019;Muranova et al, 2020).…”
Section: Protein Maintenance In Dendritic Arborizationmentioning
confidence: 99%
“…Chaperones contribute a great deal to cytoskeletal stability, which is especially important for neurons to sustain their complex processes ( Table 2; Bakthisaran et al, 2015;Nefedova et al, 2015;Nefedova et al, 2017;Kelliher et al, 2019;Muranova et al, 2019;Vallin and Grantham, 2019;Muranova et al, 2020). Many chaperones are implicated specifically in axonal morphology: manipulation of several small heat shock proteins as well as Hsp70 and 90 was found to significantly decrease synapse number in Drosophila neuromuscular junctions (Santana et al, 2020), and an Hsp70 orthologue has been found to assist in polarized trafficking of synaptic vesicle proteins to axons (Fukuzono et al, 2016).…”
Section: Protein Maintenance In Dendritic Arborizationmentioning
confidence: 99%
See 2 more Smart Citations